I am half-sick of shadows ebook - Bradley, Alan (Flavia de Luce Mystery, 2011)
“Every Flavia de Luce novel is a reason to celebrate.”— USA Today   ALAN BRADLEY, AUTHOR OF THE MOST AWARD-WINNING SERIES DEBUT OF ANY YEAR, RETURNS WITH ANOTHER IRRESISTIBLE FLAVIA DE LUCE NOVEL.   “[Alan] Bradley has created one of the most original, charming, devilishly creative and hilarious detectives of any age or any time.”—Bookreporter   It’s Christmastime, and Flavia de Luce—an eleven-year-old sleuth with a passion for chemistry—is tucked away in her laboratory, whipping up a concoction to ensnare Saint Nick. But she is soon distracted when a film crew arrives at Buckshaw, the de Luces’ decaying English estate, to shoot a movie starring the famed Phyllis Wyvern. Amid a raging blizzard, the entire village of Bishop’s Lacey gathers at Buckshaw to watch Wyvern perform, yet nobody is prepared for the evening’s shocking conclusion: a body found strangled to death with a length of film. But who among the assembled guests would stage such a chilling scene? As the storm worsens and the list of suspects grows, Flavia must ferret out a killer hidden in plain sight. BONUS: This edition includes an excerpt from Alan Bradley's Speaking from Among the Bones .   “[Flavia is] the most intrepid and charming adolescent chemist/detective/busybody in all of rural, post–World War II England.”— The Seattle Times   “Quirky and delightful . . . Flavia is a classic literary character who manages to appeal to both young and old readers equally.”—Wichita Falls Times Record News   “Bradley’s plot twists and turns delightfully.” —Fort Worth Star-Telegram   NAMED ONE OF THE BEST MYSTERIES OF THE YEAR BY THE SEATTLE TIMES